Evidence of cryptic speciation in a fossorial reptile: description of a new species of Blanus (Squamata: Amphisbaenia: Blanidae) from the Iberian Peninsula - Albert, Eva M.; Fernández, Adrián (Zootaxa, 2009)
A recent phylogeographic study using mitochondrial and nuclear DNA revealed the presence of two well defined allopatric clades of Blanus cinereus in the Iberian Peninsula. Using both univariate and multivariate statistical analyses, we show evidence of morphological differentiation between the two clades. Despite the lack of visually diagnosable morphological characters, the morphological and molecular data suggest that differentiation between the two clades was significantly enough to prevent in the past gene flow and therefore to warrant a specific status for each of the two clades. We suggest that the constraints of the subterranean life could increase the chances of experiencing cryptic speciation in worm lizards. In order to establish a taxonomic re-arrangement for the Iberian Blanus we designate a lectotype for B. cinereus from populations of central Iberia and describe a new species; Blanus mariae sp. nov. from southwestern regions of the Iberian Peninsula.